Conceptualizing an Ideal Rehabilitation Policy for Children in Conflict with the Law in Indonesia - Helda Rahmasari; Herlambang; Antory Royan Adyan; Putri Lestari (jfpublisher, 2026)
This study examines the conceptualization of an ideal rehabilitation policy for children in conflict with the law within the juvenile criminal justice system in Indonesia. Although existing studies have examined juvenile rehabilitation from legal and social perspectives, few have offered an integrated conceptual framework that connects restorative justice principles with the institutional and coordination challenges specific to Indonesia's justice system. The research employs normative legal research using statutory and conceptual approaches, analyzing legal norms, doctrines, and regulations related to child protection, restorative justice, and rehabilitation. The findings indicate that rehabilitative treatment constitutes an essential approach in handling juvenile offenders, as children require protection, guidance, and social reintegration rather than punitive treatment. However, the implementation of this approach in Indonesia still encounters several obstacles, including limited treatment facilities, insufficient professional human resources, lack of coordination among institutions, and the persistence of punitive paradigms among law enforcement officials. In addition, social stigma against children in conflict with the law often hinders the reintegration process. Therefore, an ideal policy must integrate restorative justice principles, comprehensive intervention programs, inter-agency cooperation, and community participation, structured around a coordinated institutional model rather than isolated sectoral efforts, to ensure the fulfillment of children's rights and their future development. Such a policy is expected to create a more humane juvenile criminal justice system that prioritizes the best interests of the child while preventing recidivism.